Prediction of the collapse load for moment-resisting steel frame structure under earthquake forces - Fadzli Mohamed Nazri (Penerbit Universiti Sains Malaysia, 2015)
This research book presents the fundamental work related to the prediction of collapse load for a moment-resisting steel frame (MRSF) subjected to earthquake forces.It demonstrates the extensive work in nonlinear analysis with particular reference to pushover analysis (POA) and incremental dynamic analysis (IDA), and deliberates at length the historical background for each method. More importantly, the book simplifies the collapse prediction process of a structure based on analytical expression. In addition, this book describes the MRSF which was designed according to Eurocode(s). This bookserves as a guide and reference for practitioners and students.